Toxicity of Citrate-Capped Silver Nanoparticles in Common Carp (Cyprinus carpio). (2nd October 2012) - Lee, Byoungcheun; Duong, Cuong Ngoc; Cho, Jaegu; Lee, Jaewoo; Kim, Kyungtae; Seo, Youngrok; Kim, Pilje; Choi, Kyunghee; Yoon, Junheon
Abstract : Juvenile common carp ( Cyprinus carpio ) were used as a model to investigate acute toxicity and oxidative stress caused by silver nanoparticles (Ag-NPs). The fish were exposed to different concentrations of Ag-NPs for 48 h and 96 h. After exposure, antioxidant enzyme levels were measured, including glutathione-S-transferase (GST), superoxidase dismutase, and catalase (CAT). Other biochemical parameters and histological abnormalities in different tissues (i.e., the liver, gills, and brain) were also examined. The results showed that Ag-NPs agglomerated in freshwater used during the exposure experiments, with particle size remaining <100 nm. Ag-NPs had no lethal effect on fish after 4 days of exposure. Biochemical analysis showed that enzymatic activities in the brain of the fish exposed to 200 μ g/L of Ag-NPs were significantly reduced. Varied antioxidant enzyme activity was recorded in the liver and gills. Varied antioxidant enzyme activity was recorded for CAT in the liver and GST in the gills of the fish. However, the recovery rate of fish exposed to 200 μ g/L of Ag-NPs was slower than when lower particle concentrations were used. Other biochemical indices showed no significant difference, except for NH3 and blood urea nitrogen concentrations in fish exposed to 50 μ g/L of Ag-NPs. This study provides new evidence about the effects of nanoparticles on aquatic organisms.